Human governance and firm's leverage decision: Evidence from Malaysian listed companies - Ting I.W.K.; Azizan N.A.; Kweh Q.L. (Universiti Putra Malaysia, 2023)
This paper examines the firm's leverage decision from a new perspective, namely human governance The sample covers 110 public listed companies in Bursa Malaysia for the period of 2002 to 2011. The objective of this study is to investigate the influences of human governance, namely CEO's attributes (age, founder, tenure, duality, and gender) on a firm's leverage decision through OLS regression models. The moderating effect of CEO ownership on the association between CEO personal characteristics and leverage was evaluated. From the analysis a negative relationship between CEO age, founder, gender and leverage decision and a positive impact between tenure and leverage decision was discovered. The study also shows that. CEOs owning shares in a company will more likely to take risks.The conclusion suggests that companies may increase their CEO share holdings so that CEO will align their personal interest with the ultimate goal of a company. © Universiti Putra Malaysia Press